A true relation of Virginia and Mary-land : with the commodities therein, which in part the author saw, the rest he had from knowing and credible persons in the moneths of February, March, April and May - Shrigley, Nathaniel (LLMC-digital (Series), 1669)
A brief and simply-written account of the country and the Chesapeake Bay region, with lists of the cattle, fishes, fowl, trees, and minerals to be found there.